Perancangan Sistem Informasi Penjualan, Pembelian, dan Inventori pada CV Bambi - Hartono, Sugiarto (ComTech: Computer, Mathematics and Engineering Applications, 2013)
CV Bambi considers to use IS and IT to get competitive advantage. Thus, CV Bambi needs a system that utilizes IT and records all business transactions, especially in sales, purchasing, and inventory processes so that data redundancy will be minimal. This research creates information system design of sales, purchasing, andinventory processes as well as reports that can be used by the management. Methodology used in this paper is unified process with object-oriented approach. The result is an information system design that can solve problems in data searching since all the data have been stored in a database. When sales or purchasing transaction occurs, the stock in inventory system will be automatically updated. This system will make easy the manager to read reports by using reporting feature.